Trade-offs and synergies in river-coastal restoration for the Ebro case (Spanish Mediterranean) - Agustín Sánchez-Arcilla; Luis Garrote; Vicente Gracia; Iván Cáceres; Xavier Sánchez-Artús; Nuno Caiola; Antoni Espanya; Manuel Espino; Miguel Ángel García; José María Grassa; Carles Ibáñez; David López; et al. (Nature Conservation)
The paper tackles some of the major challenges associated with coastal risk reduction, based on restored river-delta-coast continuums. The presented approach builds on the Ebro River-Delta system, located in the Spanish Mediterranean coast, where available data and results from hands-on restoration actions provide quantitative evidence on the synergies and trade-offs when implementing restoration. The work addresses the evolution of climatic- and human-induced risks driven by recent deltaic evolution, starting in the 1960s, when socioeconomic development increased and river regulation by large dams in the lower river course started. Such development has driven up freshwater demand, consequently diminishing both liquid and solid discharges in the river system, which has affected the natural deltaic evolution, compounded by sea-level-rise and changes in storminess due to global warming. Evolving erosion and flooding risks (problem symptoms) consider the decrease in sediment input to the delta and the increase in mean sea level (problem origin). To address the origin of the problem, we address sediment availability and transport in the lower river coast and reservoirs, followed by an assessment of sediment transport and deficit at the coastal fringe. The proposed solutions consider reservoir by-pass techniques, sediment mobilisation and downstream transport, as well as downstream transport capacity under present and future climates. Regarding the problem symptoms, we analyse the alternatives to enhance coastal resilience by means of restored coastal roughness resulting from embryonic dunes, lagoons and ridge and runnel topography. The analysis also considers coastal sediment recycling, based on a combination of wind and wave induced transports that provide a natural conveyor belt in dynamic equilibrium. Finally, the paper systematises the main synergies and trade-offs that must be considered in any coastal restoration plan, targeting a low carbon reduction of coastal risks while maintaining the important socio-economic assets in the river-delta-coast system. The conclusion section briefly explores the extrapolation of the proposed approach to other vulnerable coastal regions in Europe.